Inversion Of Surface Wave Phase Velocity Using New Genetic Algorithm Technique For Geotechnical Site Investigation - Hamimu, La (2011)

(untitled)
The inverse procedure of surface wave phase velocity is a complicated problem for linear inversion approach because of its multi-model and highly nonlinear nature. Therefore the use of genetic algorithm (GA) optimization technique which is one of nonlinear optimization methods is an appropriate choice to solve surface wave inversion problem having high nonlinearity and multimodality. A novel inversion procedure of GA (NIPGA) suggested in this study was presented an effective technique for surface wave phase velocity inversion.